Effect of Temperature and Feeding Time in Zero-Valent Iron (ZVI) Synthesis with Polyphenol Extracts of Kepok Banana Peels - Yusmaniar, Yusmaniar; Alfiansyah, Affif; Sutrisno, Mega (Pusat Inovasi Sains, 2022)
In this research, zero-valent iron (ZVI) was synthesized from kepok banana peels extracts as reducing agent. The fourier transform infrared spectrum showed a clear peak at a wavenumber of 600 cm-1 that could be assigned to Fe-O bond. XRD measurement results prove that ZVI has been successfully formed. The resulting ZVI particles are spherical granules with heterogeneous sizes and close together or agglomerating. Based on the results, it was found that the optimum ratio between FeSO4 and polyphenols for ZVI preparation is 4 : 1. Based on the particle size distribution analysis, it was shown that the optimum feeding temperature and time for ZVI synthesis were 25 oC and 30 minutes, respectively.